#### Answer

$\frac{1}{25}$

#### Work Step by Step

$(-125)^{-\frac{2}{3}}=\frac{1}{(-125)^{\frac{2}{3}}}=\frac{1}{(-5)^{3\times\frac{2}{3}}}=\frac{1}{(-5)^{2}}=\frac{1}{25}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\frac{1}{25}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.